Crystal structure re‐determination, spectroscopy, and photoluminescence of π‐YBO3:Eu3+. Issue 22 (30th September 2021) - Fuchs, Birgit; Schröder, Franziska; Heymann, Gunter; Siegel, Renée; Senker, Jürgen; Jüstel, Thomas; Huppertz, Hubert
Abstract: To unambiguously clarify the long‐debated crystal structure of the low‐temperature orthoborate π ‐YBO3, single‐crystals of the europium‐doped π ‐YBO3 :Eu 3+ were prepared via a high‐pressure/high‐temperature route at 7.5 GPa and 1400 °C. The structure was solved and refined in the monoclinic space group C 2/ c (no. 15) in the pseudowollastonite structure type, with the lattice parameters a =11.3407(5), b =6.5501(3), c =9.5798(4) Å, and β =113.08(2)°. This structure determination was corroborated by powder X‐ray diffraction and vibrational spectroscopy. 11 B as well as 89 Y MAS NMR spectroscopy was used to verify that our results are also accurate for the undoped π ‐YBO3 and samples with varying europium content prepared under ambient pressure conditions. Additionally, the luminescence properties of the Eu 3+ doped π ‐orthoborate were determined in comparison with these ambient‐pressure samples. Abstract : The first reliable crystal structure determination for the low‐temperature phase π ‐YBO3 revealed a monoclinic unit cell with the space group C 2/ c . Further NMR‐ and luminescence measurements proof the same structure for ambient‐ and high‐pressure samples.